2019
DOI: 10.1001/jamapediatrics.2018.3407
|View full text |Cite
|
Sign up to set email alerts
|

Placebo vs Amoxicillin for Nonsevere Fast-Breathing Pneumonia in Malawian Children Aged 2 to 59 Months

Abstract: Key Points Question Are antibiotics necessary for the treatment of nonsevere fast-breathing pneumonia in children? Findings In this double-blind, randomized clinical noninferiority trial that included 1126 HIV-uninfected children aged 2 to 59 months in a malaria-endemic region of Malawi, Africa, placebo treatment of nonsevere fast-breathing pneumonia was significantly inferior to 3 days of amoxicillin treatment with respect to treatment failure at day 4. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 32 publications
1
82
1
2
Order By: Relevance
“…Treatment failure occurred in 4% of children given amoxicillin and 7% of children given a placebo. 17 The placebo was statistically inferior to amoxicillin, although the low rates of treatment failure in each group and the high number needed to treat (n = 33) to prevent 1 case of treatment failure highlight the need to weigh risks as well as benefits of antibiotic treatment. The low rates of treatment failure are consistent with our results; however, the lack of antibiotic efficacy in our study is potentially attributable to our smaller sample size.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Treatment failure occurred in 4% of children given amoxicillin and 7% of children given a placebo. 17 The placebo was statistically inferior to amoxicillin, although the low rates of treatment failure in each group and the high number needed to treat (n = 33) to prevent 1 case of treatment failure highlight the need to weigh risks as well as benefits of antibiotic treatment. The low rates of treatment failure are consistent with our results; however, the lack of antibiotic efficacy in our study is potentially attributable to our smaller sample size.…”
Section: Discussionmentioning
confidence: 96%
“…Although there have been no trials of antibiotics versus a placebo for nonsevere pneumonia in high- resource settings, Ginsburg et al 17 performed a randomized, placebocontrolled trial of amoxicillin for the treatment of World Health Organization-defined nonsevere fastbreathing pneumonia in Malawi. Treatment failure occurred in 4% of children given amoxicillin and 7% of children given a placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategies are highly sensitive but less specific, and diagnose as pneumonia any lower respiratory disease presenting with cough, difficulty breathing and tachypnoea. Viral diseases like bronchiolitis or viral wheeze, and non-communicable diseases like allergic asthma will be diagnosed and treated as pneumonia, resulting in overprescription of antibiotics [14] and underdiagnosis and inadequate management of obstructive airway disease. The 2014 pneumonia case management revision aimed at improving pneumonia outcomes and decreasing the number of children hospitalised by classifying children with chest indrawing as having simple pneumonia [12] instead of severe pneumonia [3].…”
Section: Pneumonia: Major Killer In Children Worldwidementioning
confidence: 99%
“…The value of this recommendation was examined in children less than 6 years of age with nonsevere fast‐breathing pneumonia. A double‐blind placebo controlled study with amoxicillin found treatment failures were only 4% and 7% in the amoxicillin and placebo groups, respectively . No treatment failures by day 4 occurred in 93% of the children, and there were no differences in the frequency of treatment failures or relapses by day 14 among those without treatment failures by day 4.…”
mentioning
confidence: 99%